The reliability, and discriminative ability of the identification of functional ankle instability questionnaire, Japanese version. (January 2019) - Mineta, Shinshiro; Inami, Takayuki; Fukano, Mako; Hoshiba, Takuma; Masuda, Yuta; Yoshimura, Akane; Kumai, Tsukasa; Hirose, Norikazu
Abstract: Objective: To assess the discriminability as well as the reliability, and internal consistency of the Identification of Functional Ankle Instability questionnaire translated into Japanese (IdFAI-J). Design: Cross-sectional study. Setting: Collegiate athletic training/sports medicine clinic. Participants: Twenty bilingual and sixty-five collegiate athletes including participants with and without functional instability (FI). Main outcome measures: The sensitivity, specificity, test retest reliability, and internal consistency of IdFAI-J. Results: The optimal cutoff score between the FI and non-FI participants was >10, with an area under the curve of 0.92. We calculated high sensitivity (0.94) and specificity (0.77) at the cutoff point. For the test-retest reliability, the intraclass correlation coefficient value of the IdFAI-J was 0.96; the standard error of measurement and minimal detectable change value was 1.69 and 3.60, respectively. Cronbach's α was 0.87; there was no improvement when a particular item was deleted from the scale. Conclusions: The IdFAI-J has excellent discriminability, test-retest reliability, and internal consistency. Hence, the IdFAI-J significantly contribute to clinical practice and future research related to ankle instability in Japan. Highlights: The Japanese version of the IdFAI showed high discriminability, test retest reliability, and internal consistency. The Japanese version of the IdFAI is a reliable tool for assessing Japanese patients with functional ankle instability. The Japanese version of the IdFAI can contribute to development of the research regarding functional ankle instability in Japan.